Membrane targeting of inhibitory Smads through palmitoylation controls TGF-β/BMP signaling - Li, Wenqing (Proc Natl Acad Sci U S A, 2017)
TGF-β/BMP (bone morphogenetic protein) signaling pathways play conserved roles in controlling embryonic development, tissue homeostasis, and stem cell regulation. Inhibitory Smads (I-Smads) have been shown to negatively regulate TGF-β/BMP signaling by primarily targeting the type I receptors for ubiquitination and turnover. However, little is known about how I-Smads access the membrane to execute their functions. Here we show that Dad, the Drosophila I-Smad, associates with the cellular membrane via palmitoylation, thereby targeting the BMP type I receptor for ubiquitination. By performing systematic biochemistry assays, we characterized the specific cysteine (Cys556) essential for Dad palmitoylation and membrane association. Moreover, we demonstrate that dHIP14, a Drosophila palmitoyl acyl-transferase, catalyzes Dad palmitoylation, thereby inhibiting efficient BMP signaling. Thus, our findings uncover a modification of the inhibitory Smads that controls TGF-β/BMP signaling activity.